Digital Revolution in Madrasah Aliyah: Adaptation and Innovation in the Implementation of the Independent Curriculum - Muhamad Siswanto (TEKILA: Journal of Language Teaching and Literature, 2024)
Education in Indonesia continues to transform with the implementation of the Merdeka Curriculum, which provides flexibility to tailor learning to the needs of students. Digital technology plays an important role in enhancing the quality of education and developing 21st-century skills. Despite challenges such as access gaps and teacher readiness, digital technology offers opportunities to create more interactive and relevant learning experiences. With the right support, madrasahs can leverage technology to prepare students for future challenges. The research method used is qualitative with a literature study. The findings of this research are as follows: digital technology has great potential to improve the quality of education in Madrasah Aliyah, especially with the implementation of the Merdeka Curriculum, which allows for more flexible, competency-based learning that aligns with technological developments. This provides opportunities for students to learn independently, creatively, and develop the 21st-century skills that are highly needed in the workforce. However, challenges in the implementation of digital technology include access gaps to infrastructure and resources, as well as the need to improve teachers' competencies in utilizing technology effectively. Nevertheless, the opportunities provided by digital technology are vast, in creating inclusive, adaptive, and data-driven learning, as well as supporting the holistic development of students' character. The Merdeka Curriculum plays a key role in encouraging the adoption of digital technology in madrasahs, offering the freedom to integrate technology according to local needs, and preparing students to face global challenges. With this policy, madrasahs can optimize technology to create more engaging, relevant, and impactful educational experiences that contribute to students' development in the future